Disability progression in multiple sclerosis patients using early first‐line treatments. (11th June 2022) - Lefort, Mathilde; Vukusic, Sandra; Casey, Romain; Edan, Gilles; Leray, Emmanuelle; ,
Abstract: Background and purpose: Therapeutic management of relapsing–remitting multiple sclerosis (RRMS) has evolved towards early treatment. The objective was to assess the impact of early treatment initiation on disability progression amongst RRMS first‐line‐treated patients. Methods: This study included all incident RRMS cases starting interferon or glatiramer acetate for the first time from 1 January 1996 to 31 December 2012 ( N = 5279) from 10 MS expert Observatoire Français de la Sclérose en Plaques centres. The delay from treatment start to attaining an irreversible Expanded Disability Status Scale (EDSS) score of 3.0 was compared between the early group ( N = 1882; treated within 12 months following MS clinical onset) and the later group using propensity score weighted Kaplan–Meier methods, overall and stratified by age. Results: Overall, the restricted mean time before reaching EDSS 3.0 from treatment start was 11 years and 2 months for patients treated within the year following MS clinical onset and 10 years and 7 months for patients treated later. Thus, early treated patients gained 7 months (95% confidence interval [CI] 4–11 months) in the time to reach EDSS 3.0 compared to patients treated later (treatment start delayed by 28 months). The difference in restricted mean time was respectively 6 months (95% CI 1–10 months) and 14 months (95% CI 4–24 months) in the ≤40 years age group and in the >40 years age group, in favour of the early group. Conclusions: Early treatment initiation resulted in a significant reduction of disability progression amongst patients with RRMS, and also amongst older patients. Abstract : Using the French MS Registry (Observatoire Français de la Sclérose En Plaques, OFSEP), the real‐life effectiveness of early first‐line treatment initiation was assessed amongst 5279 patients included over the period 1996–2012. Early treated patients, that is, patients in the first year following MS clinical onset, were compared to later treated patients, and the two groups were made comparable using propensity scores. Our work confirmed the overall benefit of early treatment on disability progression but also demonstrated such benefit in the population of patients developing MS after 40 years of age.